2011
DOI: 10.2224/sbp.2011.39.8.1021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Family-based Intervention Model On Internet-addicted Chinese Adolescents

Abstract: We aimed to evaluate the effectiveness of a family-based intervention program for Internet addiction in Chinese adolescents. Adolescents (N = 57), diagnosed as having Internet addiction, were divided randomly into an intervention group (n = 28) and a control group (n = 29). Participants in the intervention group participated in a 14-session family-based group intervention while participants in the control group received conventional group therapy only. Assessment tools were administered to both groups at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 0 publications
3
55
0
1
Order By: Relevance
“…Based on prior family group intervention practices in treating adolescent psychopathology (Chien & Chan, 2013;McDonell & Dyck, 2004;Zhong et al, 2011), the current study is the first to our knowledge to apply the approach of MFGT in treating adolescents' Internet addiction. The adolescents' Internet addiction rate dropped from 100% at the baseline assessment to 4.8% at the end of the intervention and remained at 11.1% at the three-month follow-up assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on prior family group intervention practices in treating adolescent psychopathology (Chien & Chan, 2013;McDonell & Dyck, 2004;Zhong et al, 2011), the current study is the first to our knowledge to apply the approach of MFGT in treating adolescents' Internet addiction. The adolescents' Internet addiction rate dropped from 100% at the baseline assessment to 4.8% at the end of the intervention and remained at 11.1% at the three-month follow-up assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research also proved that a good relationship and communication with parents are protective factors for adolescents from Internet addiction (Kim, Jeong, & Zhong, 2010;Van den Eijnden et al, 2010). Family members involved in interventions facilitate the process of recovery and help the addict maintain a lasting effect of intervention after sessions (Liddle, 2004;Zhong et al, 2011). Grounded in family system theory and integrated in family and group therapy, multi-family group therapy (MFGT) was proposed as a promising new approach to treat Internet addiction behaviors, but no empirical study was conducted (Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Smit et al, 2008;Kaminski, Valle, Filene & Boyle, 2008) indicated that these interventions have demonstrated efficacy in preventing substance use and other child problem behaviors. These positive results have been reported in different settings (Aalborg et al, 2010;Letarte, Normandeau & Allard, 2010;Redmond et al, 2009;Henggeler & Schoenwald, 2011;Brook, McDonald & Yan, 2012;Donavan, Wood, Frayjo, Black & Surette, 2012), target groups (Mindel & Hoefer, 2006;Orte, Touza, Ballester & March, 2008;McDaniel, Braiden, Onyekwelu, Murphy & Regan, 2011;Posthumus, Raaimakers, Maassen, Engeland, & Matthys, 2012;Kumpfer, Whiteside, Greene & Allen, 2010), cultures (Skärstrand, Larsson & Andréasson, 2008;Pérez, et al, 2009;Kumpfer, Xie & O'Driscoll, 2012;Brotman et al, 2009;Ortega, Giannotta, Latina & Ciairano, 2012) and addicted behaviours (Trudeau, Spoth, Randall & Azevedo, 2007;Zhong, et al, 2011;Donovan et al, 2012). …”
Section: Objeto Y Alcance De La Presente Revisión Bibliográficamentioning
confidence: 72%
“…Por ello, los componentes más importantes de estos programas incluyen la interacción positiva padres-hijos, enseñar a los padres a usar el "tiempo fuera", ofrecer reafirmación positiva, enseñar habilidades de comunicación y fijación de reglas. Las habilidades de resistencia social y a los coetáneos, el desarrollo de normas de conducta y buscar la compañía de coetáneos positivos, también se pueden abordar desde un programa universal basado en la familia para la prevención de las toxicodependencias (Lochman y Steenhoven, 2002 (Aalborg et al, 2010;Letarte, Normandeau y Allard, 2010;Redmond et al, 2009;Henggeler y Schoenwald, 2011;Brook, McDonald y Yan, 2012;Donavan, Wood, Frayjo, Black y Surette, 2012), grupos meta (Mindel y Hoefer, 2006;Orte, Touza, Ballester y March, 2008;McDaniel, Braiden, Onyekwelu, Murphy y Regan, 2011;Posthumus, Raaimakers, Maassen, Engeland, y Matthys, 2012;Kumpfer, Whiteside, Greene y Allen, 2010), culturas (Skärstrand, Larsson y Andréasson, 2008;Pérez, et al, 2009;Kumpfer, Xie y O'Driscoll, 2012;Brotman et al, 2009;Ortega, Giannotta, Latina y Ciairano, 2012) y conductas adictivas (Trudeau, Spoth, Randall y Azevedo, 2007;Zhong et al, 2011;Donovan et al, 2012).…”
Section: Introductionunclassified